(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Indian engineering education has been subjected to swift and radical change over the recent years, especially with the increase in private institutes across the length and breadth of the nation. This paper aims at determining the gap between expectations and perceptions of engineering education from the perspective of students. Servqual instrument was used to gather data from 189 students from new age private engineering institutes. Reliability tests, correlation and regression were done to ensure the validity of the data collected. Further, gap analysis was done to check out for the existing gaps. Correlation was also done to find out the relationship between the dimensions of education quality and overall satisfaction of the students, and finally regression was done to find out the actual determinants of students satisfaction. The is helpful for both engineering institutes and other academicians as it helps in disentangling the perceptions about education quality from the students point of view. This will largely help the upcoming private institutes to design their services in the best possible manner.